Engineering and Functional Evaluation of Neutralizing Antibody Fragments Against Congenital Toxoplasmosis. (7th August 2021) - di Tommaso, Anne; Juste, Matthieu O; Lakhrif, Zineb; Mévélec, Marie-Noëlle; Borowczyk, Coraline; Hammeni, Pierre; Désoubeaux, Guillaume; Van Langendonck, Nathalie; Debierre-Grockiego, Françoise; Aubrey, Nicolas; Dimier-Poisson, Isabelle
Abstract: Maternal-fetal transmission of Toxoplasma gondii tachyzoites acquired during pregnancy has potentially dramatic consequences for the fetus. Current reference-standard treatments are not specific to the parasite and can induce severe side effects. In order to provide treatments with a higher specificity against toxoplasmosis, we developed antibody fragments—single-chain fragment variable (scFv) and scFv fused with mouse immunoglobulin G2a crystallizable fragment (scFv-Fc)—directed against the major surface protein SAG1. After validating their capacity to inhibit T. gondii proliferation in vitro, the antibody fragments' biological activity was assessed in vivo using a congenital toxoplasmosis mouse model. Dams were treated by systemic administration of antibody fragments and with prevention of maternal-fetal transmission being used as the parameter of efficacy. We observed that both antibody fragments prevented T. gondii dissemination and protected neonates, with the scFv-Fc format having better efficacy. These data provide a proof of concept for the use of antibody fragments as effective and specific treatment against congenital toxoplasmosis and provide promising leads. Abstract : To prevent maternal-fetal transmission of Toxoplasma gondii tachyzoites, antibody fragments have been developed. Their use as effective and specific treatment against congenital toxoplasmosis provides promising leads.